A Research on the effect of social media on tendency to entrepreneurship and business establishment (Case Study: Active Iranian Entrepreneurs in Social Media) - Tosifyan, Masoud; Tosifyan, Saeed (Ital Publication, 2017)
This research was done with the aim to investigate the effect of social media on tendency to entrepreneurship and business establishment. The aim of applied research and methods used in this survey was a descriptive survey research. A standard questionnaire was used to collect relevant data in this study. The reliability of each questionnaire was estimated 0.779, 0.806 and 0.798. The population study is Iranian entrepreneurs who are active in social media and number of them is uncertain; A sample of 120 active Iranian entrepreneurs were selected as target and a questionnaire was distributed among these individuals. To collect the information and necessary data to evaluate the hypotheses of the research, a questionnaire and SPSS and LISREL software were evaluated.Â At inferential comprehension level, techniques of Kolmogorov-Smirnov test for being normal, Pearson correlation test and structural equation modelling were used to test the hypotheses. Based on the results, the hypotheses were accepted.